Implementation of Finger Puppet Use to Improve Children’s Speaking Skills in Group A at Al Hidayah III Kindergarten, Madiun City - Septiana, Nadia Putri; Chasanatun, Fida; Susari, Hermawati Dwi (Kiddie: Early Childhood Education and Care Journal, 2026)
This study aimed to determine the implementation of finger puppet media in improving the speaking skills of Group A children at TK Al-Hidayah III Madiun City. Speaking skills are an important aspect of early childhood language development that should be stimulated through engaging learning activities appropriate to children's characteristics. Initial observations indicated that some children lacked confidence and fluency in speaking. This study employed a collaborative Classroom Action Research (CAR) model developed by Kemmis and McTaggart, which was conducted in two cycles consisting of planning, action, observation, and reflection stages. The research subjects were 14 children aged 4–5 years in Group A. Data were collected through observation, interviews, and documentation. The data were analyzed using descriptive qualitative and quantitative methods with simple percentage analysis. The findings showed that the use of finger puppet media improved children's speaking skills, as indicated by the increase in learning mastery from 71.43% in the pre-cycle to 78.57% in Cycle I and 100% in Cycle II. Therefore, finger puppet media is effective in improving the speaking skills of Group A children at TK Al-Hidayah III Madiun City.